Association of Parental Obesity and Diabetes Mellitus With Circulating Adipokines in Nonobese Nondiabetic Offspring. Issue 7 (July 2017) - Zachariah, Justin P.; Quiroz, Rene; Enserro, Danielle; Andersson, Charlotte; Keaney, John F.; Sullivan, Lisa M.; Vasan, Ramachandran S.
Abstract : Background: Adipokines are implicated in the development of obesity‐related traits. We hypothesized that nonobese participants without diabetes mellitus (DM) whose parents were obese or had DM would have altered circulating adipokines compared with those without parental history of these conditions. Methods and Results: Participants in the community‐based Framingham Third Generation cohort who were not obese (body mass index <30) and not diabetic with both parents in the Framingham Offspring cohort were included in this analysis (n=2034, mean age 40 years, 54% women). Circulating concentrations of fetuin A, RBP4 (retinol binding protein 4), FABP4 (fatty acid binding protein 4), leptin, LEP‐R (leptin receptor), and adiponectin were assayed. Parental DM was defined as occurring before age 60 years, and obesity was defined as body mass index ≥30 before age 60 years. General estimating equations were used to compare concentrations of adipokines among participants with 0, 1, or 2 parents affected by obesity or DM (separate analyses for each), adjusting for known correlates of adipokines. Overall, 44% had at least 1 parent who was obese and 15% had parents with DM. Parental obesity was associated with higher serum levels of FABP4 and LEP‐R in their offspring ( P =0.02 for both). Parental DM was associated with lower adiponectin but higher RBP4 concentrations in offspring ( P ≤0.02 for both). Conclusions: In our community‐based sample, a parental history of DM or obesity was associated with an altered adipokine profile in nonobese nondiabetic offspring. Additional studies are warranted to evaluate whether such preclinical biomarker alterations presage future risk of disease.